The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1109/access.2021.3070192
|View full text |Cite
|
Sign up to set email alerts
|

Calculating Millimeter-Wave Modes of Copper Twisted-Pair Cables Using Transformation Optics

Abstract: have contributed equally. † Joint supervision of this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…As the dielectric constant increases, the propagation constant of the supported modes increases as well. From (10), the resulting stop band is expected to shift to lower frequencies. Similarly reducing the dielectric constant causes the stop band to shift to higher frequencies.…”
Section: Effects Of Dielectric Constantmentioning
confidence: 99%
See 1 more Smart Citation
“…As the dielectric constant increases, the propagation constant of the supported modes increases as well. From (10), the resulting stop band is expected to shift to lower frequencies. Similarly reducing the dielectric constant causes the stop band to shift to higher frequencies.…”
Section: Effects Of Dielectric Constantmentioning
confidence: 99%
“…Hence, it was suggested to exploit other modes supported by copper cables [8]. First studies hinted at data rates up to terabit/s using multiple modes in the low THz frequency range simultaneously [9], [10]. However, the simulated data rate again quickly decreased with link length due to high intrinsic losses of the modes involved in propagation.…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent paper 14 , 1 Tbps data rate was achieved in a two-wire line with metal sheet up to 10 m distance by using a similar vectoring technique to exploit the modal diversity of the waveguide at 200 GHz. Furthermore, Hejazi et al 15 investigated the millimetre-wave spectrum in TP cables by using transformation optics based numerical simulations to calculate the properties of the waveguide modes and their spatial harmonics. This paper also showed that 1 Tbps can be achieved over a twisted-pair with a plastic sheath up to 10 m. Although there are several papers on investigating millimetre wave and THz frequency spectrum over the copper network, experimental work is still at its infancy.…”
Section: Introductionmentioning
confidence: 99%